Utilization of screw-pine leaf bio-composite for home accessories - Zainol, Izyan Syamimi (2019)
Screw-pine leaf is used in traditional craft product in Malaysia and some part of South East Asia. This traditional material is well-known as mengkuang in Malays is an appropriate material to produce the daily necessity products such as cloth storage box, food cover, mat and bag. There are three types of screw-pine leaf used in Malaysia which the usage of each of the screw- pine leaf in the craft product of is variety due to the differences of the leaves strength. The research focus on Pandanus atrocarpus locally called mengkuang minyak and it is the most durable among the three types of screw-pine leaf. There is an issue about the possibility on the extinction of the mengkuang plaiting heritage in Malaysia. The young generation has less concern in continuity of this heritage skill and business. It is the derivation issue of the research problem that shows the underutilization of the screw-pine leaf as material and less application on high value added product such as home accessories. Working together with community from Kampung Bentan , Pahang and Kampung Air Molek, Melaka, the researcher conducted a study on producing a screw-pine leaf bio-composite that will encourage and promote the utilization of the screw-pine leaf in high value product. However, in order to apply the screw-pine leaf on high value added product as bio- composite material, documented data is needed on the properties of this material. Through the early process of producing the screw-pine leaf bio-composite, the researcher identify the needs of treatments on screw-pine leaf. Several experiment included alkali treatment (sodium hydroxide), acid treatment (boric acid) and non-treatment woven is conducted. The sample of the screw-pine leaf bio-composite is produced by using the lamination hand lay–up process of cold press method to introduce the screw-pine leaf bio-composite to the rural business. The testing on tensile and flexural strength is studied to prove the screw-pine leaf can be applied as material as any other natural fiber bio- composite. The testing conducted referring to the ASTM Standard; tensile strength ASTM D638 and flexural strength ASTM D790-07. The test shows the highest tensile strength is record by acid treated screw-pine leaf bio-composite with 1.878 MPa and 1.877 GPa for the tensile young modulus. While, the flexural strength is 8.57 MPa and 0.538 GPa for the flexural young modulus is recorded by untreated screw-pine leaf bio- composite. Comparison to banana leaf bio-composite with similar fabrication process, the screw-pine leaf bio-composite in this study shows better mechanical properties. The researcher applied the screw-pine leaf bio-composite in various design artefacts consists of furniture, lighting and small decorative products. The artefact is validated through a survey that studying the acceptance of the screw-pine leaf bio-composite material in product design based on the listed attributes. The attributes were collected through brainstorming from a group of designers that experienced in marketing a product. The result of the validation survey shows an acceptance from public and designers especially on the form and the story as traditional material of the proposed product. Also, the survey shows that, there are high-potential marketability for the product with the application of screw-pine leafs. Particularly for the small decorative product and the survey shows that the lighting product is the most suitable to apply the screw-pine leaf bio-composite. The survey also shows the demand that position the screw-pine leaf product in the market. Hence, by proposing an alternative material of screw-pine leaf bio-composite, the range of screw-pine leaf product based can be various. With this kind of approach, there are high possibilities that the rural business of screw-pine leaf heritage can be revitalized and encourage the utilization of the screw-pine leaves.